Analysis of IL1B, TAP1, TAP2 and IKBL polymorphisms on susceptibility to tuberculosis (2006)
Genetic determinants of human susceptibility to tuberculosis (TB) have not been completely elucidated. Interleukin-1 beta (IL-1?) and the inhibitor of kB-like (IkBL) are important molecules that participate in the inflammatory response required for the immunological control of a broad spectrum of infectious agents. The transporter associated with antigen processing (TAP) is involved in the antigen processing via major histocompatibility complex class I molecules and in turn might regulate the T-cell response against Mycobacterium tuberculosis. To better characterize the host genetic factors determining the susceptibility to TB, we evaluated the influence of functional polymorphisms in IL1B, TAP and IKBL genes on the risk of developing pulmonary TB in a Northwestern Colombian population, an endemic area of M. tuberculosis infection. A total of 122 TB patients and 166 healthy controls (N = 166) negative for human immunodeficiency virus infection were examined for IL1B-511 and +3953, TAP1 and TAP2 and IKBL+738 polymorphisms. Univariate analysis disclosed significant differences between patients and controls for IL1B+3953 polymorphism. After unconditional logistic regression analysis, a strong protection conferred by IL1B+3953 T-allele-carrying genotypes was observed. A trend between TAP2*0201 allele and disease was observed. Association between IL1B-511, TAP1 or IKBL polymorphisms and TB disease was not found. These results indicate that a functional polymorphism in the IL1B gene influences the susceptibility to TB and suggest a role for IL-1? in the pathogenesis of mycobacterial infection. © 2006 Blackwell Munksgaard.